ANALISIS KONTRIBUSI PENERIMAAN PAJAK DAERAH SEBAGAI SALAH SATU SUMBER PENDAPATAN ASLI DAERAH (PAD) KABUPATEN MALANG (STUDI PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET KABUPATEN MALANG) - Fauziah, Isfatul (Jurnal Mahasiswa Perpajakan, 2014)
The purpose of this study are to determine the contribution of each type of local tax revenue (PAD) in Malang, to determine the level of effectiveness achieved for each type of tax in the District of Malang. The development of a nation always needs great costs because fund support is very influential to the developmental activities, especially those conducted by local government to the locality. Malang District has recognized the fact that some sources of Local Genuine Income must be exploited, and one of them is local tax. Huge revenue potential from local tax in Malang District must be developed and managed properly. It is then reasonably important to understand contribution and effectiveness of local tax revenue in Malang District as a source of Local Genuine Income. Therefore, the objective of research is to comprehend contribution and effectiveness of local tax revenue as a source of Local Genuine Income in Malang District. Local tax revenue in three-year period from 2011 to 2013 is then examined. Keyword: Contribution, Local tax, Local Genuine Income